Thickness and temperature dependent thermoelectric properties of Bi87Sb13 nanofilms measured with a novel measurement platform - Linseis; Voelklein, F.; Reith, Heiko; Huehne, R.; Schnatmann, L.; Nielsch, Kornelius; Woias, P. (Semiconductor Science and Technology, 2018)
The temperature and thickness dependent thermoelectric properties of Bi87Sb13 nano-films with a thickness from 84 nm to 282 nm have been studied in a temperature range from 110 K up to 450 K. The films have been prepared by thermal evaporation of the raw material from an Al2O3 coated tungsten boat under vacuum conditions of at least 10-6 mbar. The measurements have been performed using a novel measurement platform, which allows the nearly simultaneous characterization of the thermal conductivity, electrical conductivity, the Seebeck coefficient and the Hall coefficient. All properties are measured in the in-plane direction at the same sample within one measurement run, avoiding many sources of uncertainties and allowing the calculation of the direction dependent, in-plane thermoelectric figure of Merit ZT with high precision. The maximum ZT value of 0.28 has been obtained for the thickest sample at a temperature of 265 K. All comparative measurements have been performed after an initial thermal annealing step, as the heat treatment shows a strong impact on the thermoelectric performance of the films.
CRIS-Team Scopus Importer:2022-04-14
Keywords: bismuth antimony; hall coefficient; resistivity; seebeck effect; thermal conductivity; thermoelectric; thin film